A New Iron Age Chamber Tomb near Catak, South of Van Lake - (:unkn) unknown (PEETERS, 2016)
Our knowledge of the period preceding the Kingdom of Urartu, which was established in the mid-ninth century BC with Van as its centre, is quite limited. From Assyrian sources from the reign of Shalmaneser I on, we learn about communities living on the high plateaus of Eastern Anatolia. However, archaeological research in the region has provided little information. This period, known as pre-Urartian in the Lake Van basin, is evaluated here in the light of data from the Ernis, Karagunduz, Dilkaya, and Yoncatepe necropolises. Archaeological research in Lake Van basin indicates a tradition of chamber tombs. The latest example of an underground chamber tomb built of stones is the Catak chamber tomb. The burials in the tomb bear anthropological features suggesting that the buried individuals belonged to the same family, and they provide new data on grave goods and burial practices. In addition, it can be argued that the social structure hypothesised in relation to burials to the north and east of the lake can also be applied to burials south of Lake Van.
Keywords: Eastern Anatolia; Early Iron Age; Van; Chamber Tomb; Catak; Urartian